The intensity of menopausal symptoms is associated with episodic memory in postmenopausal women. (3rd July 2016) - Triantafyllou, N.; Armeni, E.; Christidi, F.; Rizos, D.; Kaparos, G.; Palaiologou, A.; Augoulea, A.; Alexandrou, A.; Zalonis, I.; Tzivgoulis, G.; Lambrinoudaki, I.
Abstract: Objective: The adaptation of the brain to aging is subject to the impact of psychological and environmental factors and possibly climacteric symptomatology. We aimed to determine the association of climacteric symptomatology with different aspects of episodic memory in a sample of Greek menopausal women. Methods: This cross-sectional study included 39 postmenopausal women with subjective memory complaints. Memory performance was evaluated using the Hopkins Verbal Learning Test (HVLT) and the revised Brief Visuospatial Memory Test (BVMT), assessing verbal and visuospatial episodic memory, respectively. We evaluated general cognitive status using the Mini-Mental State Examination (MMSE) and the Clock Drawing Test. Menopausal symptoms were assessed using Greene's Climacteric scale. Results: In the multivariate approach, vasomotor symptoms predicted independently HVLT (retained percentage and delayed recall: b-coefficient = −0.568, p = 0.009 and b-coefficient = −0.563, p = 0.012, respectively). Psychological symptoms predicted independently MMSE (b-coefficient = −0.391, p = 0.024); and in combination with free estrogens (logFEI), psychological symptoms predicted BVMT (total and delayed recall: b-coefficient = −0.558, p = 0.001 and b-coefficient = −0.474, p = 0.005) and HVLT discrimination index (b-coefficient = −0.390, p = 0.023). Combined symptomatology predicted independently MMSE (b-coefficient = −0.457, p = 0.006) and HVLT total (b-coefficient = −0.557, p = 0.034); combined symptomatology predicted in combination with logFEI scores of BVMT total (b-coefficient = −0.593, p < 0.001), BVMT delayed recall (b-coefficient = −0.492, p = 0.002). Conclusion: The intensity of psychological, vasomotor and combined climacteric symptoms predicted cognitive performance in this sample of postmenopausal women. A differential contribution of vasomotor symptoms to episodic memory is described, with the negative impact being more pronounced in visuospatial rather than verbal episodic memory.